Learning-Related Emotions in First-Year International Students: Investigating Affective, Cognitive, Motivational, and Physiological Components - Tempelaar, Dirk; Niculescu, Alexandra (Social Education Research, 2025)
The component process model of achievement emotions views learning emotions as interconnected psychological processes comprising affective, cognitive, motivational, and physiological components. Based on this framework, the Achievement Emotion Questionnaire (AEQ) was developed as a key self-report tool for measuring specific achievement emotions in educational settings. Despite widespread use of the AEQ in empirical research, only a few studies have explicitly validated its component structure. This study aims to address that gap by examining the component structure of learning emotions measured with the AEQ. We applied both confirmatory and exploratory factor analyses to a large dataset of responses to evaluate the robustness of the component structure. Our sample included 14,456 first-year students enrolled at a Dutch business and economics school across the academic years 2010/2011 to 2023/2024. Most importantly, findings reveal a significant issue: the multi-component model does not hold for at least one crucial aspect—the physiological component of the positive learning emotion, enjoyment. This component does not align well with the others and fails to adhere to a fundamental assumption of the control-value theory of achievement emotions, which posits that academic control, along with intrinsic and extrinsic value, serves as a proximal antecedent for both emotions and their components. Additionally, hierarchical regression models were used to examine the predictive strength of proximal antecedents across components, with a specific focus on gender effects and their interactions with emotion components. Gender effects uncover that while female students generally experience higher anxiety and hopelessness and lower boredom compared to male students, their emotional patterns in relation to the proximal antecedents are largely similar to those of male students in comparable situations.